Type A Aortic Dissection Masquerading as an Inferior Myocardial Infarction - Hussain, Azhar; Rossi, Alessia; Smith, Alexander; Lopez-Marco, Ana; Khalil, Amina; Roberts, Neil (AORTA, 2021)
Type A aortic dissection is a life-threatening condition with a wide range of clinical manifestations. Dissection can sometimes mimic an acute myocardial infarction due to similar presenting symptoms and initial clinical investigations. We report the case of a 52-year-old male who presented with an inferior ST-segment elevation myocardial infarction with two drug-eluting stents inserted as a stabilizing intervention prior to surgical repair of an acute aortic dissection.
Keywords: aortic dissection; myocardial infarction; percutaneous coronary intervention